Prinsip Etika Kristen sebagai Kerangka Moral dalam Bisnis E-Commerce di Era Digital: Studi Literatur - Yosua Gunawan; Yanto Paulus Hermanto; Josep Tatang (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
The development of e-commerce in the digital era has created broad business opportunities while also generating ethical challenges that intersect with legal aspects, such as fraud, information manipulation, fake reviews, monopolistic practices, and consumer exploitation. This study employs a qualitative method through normative–conceptual literature review. The findings indicate that the principles of honesty, love, justice, and stewardship can serve as guidelines for sellers in making fair business decisions, building consumer trust, serving customers empathetically, and supporting small business actors. These principles have the potential to strengthen sellers’ integrity and reputation while fostering a sustainable, inclusive digital ecosystem aligned with spiritual values. Therefore, e-commerce sellers who uphold Christian ethical principles can play a role as agents of social and moral transformation in the digital era.